Youth unemployment in the system of social economic relations - Romanika, Tetiana (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
Unemployment is a complex and socially acute macroeconomic problem. Youth unemployment in the current transformations of social and labor relations becomes especially relevant and requires a comprehensive study. Scientific understanding of the content and forms of youth unemployment is an important basis for developing practical measures to reduce it and effectively use the potential of youth in socio-economic development. The subject of the article is the phenomenon of youth unemployment, the aim is to reveal the features of modern youth unemployment in the current transformations of the labor market and develop practical measures to reduce it. To achieve this goal, the following tasks were set and solved: the reasons for the tendency to increase youth unemployment in the context of digitalization of the economy; the basic forms in which there is youth unemployment are characterized; the structure of youth unemployment is analyzed; the main directions of overcoming unemployment due to the improvement of youth policy in the labor market are proposed. To solve these problems, the following research methods were used: general scientific foundations and fundamental provisions of economic theory, interdisciplinary approach to a more meaningful disclosure of the unemployment category, behavioral scientific approach used to explain the behavior of young people in the labor market. The results of the study are: substantiation of the institutional imperfection of the labor market, which creates contradictions in the system of youth unemployment; characteristics of social exclusion of youth and other negative trends in the labor market in Ukraine. Conclusions. Ways to minimize youth unemployment through the formation of an innovative model of social and labor relations, the cultivation of inclusive institutions and active youth policy of the state are substantiated.